Cavendish banana-cacao intercropping system willingness to adopt of small banana farmers in Davao del Norte - Infiesto, Ker Denzel G.; Acuna, Thaddeus R.
Cavendish banana production contributes a substantial value to the banana industry because of its high demand in the international market. The production of the commodity is centered in Davao region. However, the industry has experienced challenges in the past few years that have a potential of occurring again. The Federation of Cooperatives in Mindanao (FEDCO), an organization of banana-based cooperatives initiated the Cavendish banana-cacao intercropping system to help the farmers cope with the effects of the previous challenges. This paper assesses the willingness of the small banana farmers in Davao del Norte to adopt the banana-cacao intercropping using binomial logit. At present, there are five intercropping systems done by FEDCO and its co-operators. Each has a unique design and arrangement of crops. The intercropping system can give a net income that is 0.65% and 43.68% higher compared to the incomes from pure Cavendish and pure cacao respectively. However, most of the farmers have negative perception about the intercropping system due to their insufficient knowledge about the nature of cacao. They don't have enough knowledge about the intercropping project of FEDCO as well. Using logit, the probability of adoption of small banana farmers is 33.33% which is quite high despite their small knowledge about the project. For them, the intercropping project could provide them additional income. In order to encourage more farmers to adopt, FEDCO should intensify its information and dissemination about it.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines, Mindanao
Keywords: Cavendish banana; Cacao